Facial bone lengthening apparatus with expander and miniplates - Viterbo, Fausto [UNESP]; Zanini, Silvio Antonio [UNESP] (Associação Paulista de Medicina - APM, 1994)
Since 1869, bone lengthening has been pursued; when Langenbeck (13) tried growing a shortened bone extremity utilizing for this an arteriovenous fistula in the thigh. At the begining of this century, codovilla (1905) (5,14) introduced bone lenghtening methods for lower limbs.

Os autores propõem a utilização de um alongador ósseo composto de duas miniplacas. Através de uma válvula remota o expansor seria enchido e a distensão da bolsa promoveria afastamento das miniplacas e consequentemente das extremidades ósseas
Keywords: Bone lengthening; expander; silicone